Coconut Sugar Quality Control Analysis of Home-Industry in Central Java - Susanti Wiwi (EDP Sciences, 2021)
Coconut sugar is a potential trade commodity, and Indonesia is one of the biggest exporters in the world. There were some problems such as the use of raw material was not optimum and some quality issues. The study aims to identify the defective product and evaluate the current process capacity at Ngudi Lestari as one of the biggest home-industry in Central Java. The method was use the Six Sigma Method through DMAIC tools. The data was used primary data from 28 times production during seven days through the observation process. The finding showed that there were nine potential critical to quality that affects sugar. The control chart showed that production in Ngudi Lestari still uncontrollable. It was indicated by the process that out of control limit was about 75%. The result of the sigma value was sufficient, which was 4.39. It had reached the average sigma level of industry in the United States. The defective products were caused by raw materials, labor, equipment, and production process. The raw material was one factor that had a significant effect on the quality of coconut sugar.